Resenha de Aldo Dinucci. Manual de Estoicismo: a visão estoica do mundo. Campinas: Editora Auster, 2023, 144pp., ISBN 9786587408651 - Nascimento, Joelson (Revista Archai, 2025)
Resenha de Aldo Dinucci. Manual de Estoicismo: a visão estoica do mundo. Campinas: Editora Auster, 2023, 144pp., ISBN 9786587408651